Book Reviews - NEDELEA, Luciana; PÁZSINT, Annamária-Izabella; COCIȘ, Horaţiu; ANDREICA, Gabriel (Studia Universitatis Babeș-Bolyai Historia, 2016)
Alexandru Diaconescu, “«Clasicismul» în plastica minoră din Dacia Romană”, Cluj-Napoca, Editura Mega, 2013, 240 p., ISBN 978-606-543-425-7. Cristina-Georgeta Alexandrescu (ed.), „Jupiter on your side. Gods and humans in antiquity in the Lower Danube area”. Accompanying publication for the thematic exhibitions in Bucharest, Alba Iulia and Constanţa, May – September 2013, Bucharest, Institutul de Arheologie Vasile Pârvan, 2013, 295 p., ISBN 978-973-0-15140-4 Paperback. George Cupcea, „Professional Ranks in the Roman Army of Dacia”, BAR International Series, Archaeopress, 2014, 154 p., ISBN 978-1-4073-1325-2. Gelu Florea (ed.), “Matriţa de bronz de la Sarmizegetusa Regia”, Cluj-Napoca, Editura Mega, 2015, 168 p, ISBN 978-606-543-604-6.